Mihailo Petrović Alas' contribution to development of interest for mathematics - Mirko R. Dejić (University of Belgrade, Teacher Education Faculty, 2020)
Apart from his great creative work in mathematical science, Mihailo Petrović Alas, one of the greatest Serbian mathematicians, managed to write several works of methodological character which were intended for teachers at elementary and secondary schools. In these works Mihailo Petrović's aim was to popularize mathematics and show how teachers can also be creative and inventors within the domain of teaching. We give an overview of these works in our paper and acquaint the readers in detail with his interesting application of the Pythagorean theorem. A short retrospect of the complete scientific and pedagogical opus of Mihailo Petrović Alas will also be given in the paper.